Nadir Fakat Önemli Bir Acil: Dil Kökü Absesi - Ozbay, Musa; Bakır, Salih; Kınıs, Vefa; Yorgancılar, Ediz (Fırat University, 2012)
Dil kökü absesi çok nadir görülen bir klinik antitedir. Üst solunum yolunun daralmasına bağlı olarak hayatı tehdit edebilir. Dilde şişme, disfaji ve dispne ile gelen hastalarda dil kökü absesi düşünülmelidir. Pürülan materyalin iğne ile boşaltılması tanı ve tedavi için yeterlidir. Dil kökü absesine bağlı 2 haftadır disfaji, dispne ve dilde şişme şikayetleri olan bir vakayı sunuyoruz.

Abscess of the tongue base is a very rare clinical entity. It may be life-threatening according to narrowing of upper airway. Tongue base abscess should be considered in patients who presented with tongue swelling, dysphagia and dyspnea. Aspiration of the purulent material by needle is adequa-te both for treatment and diagnosis. We present a case of tongue base abscess presented with dysphagia, dyspnea and swelling of tongue for 2-weeks.
A Rare But Important Emergency: Abscess of The Tongue Base